DEVELOPMENT OF VILLAGE APPARATUS PERFORMANCE IN REALIZING SERVICE IMPROVEMENT FOR THE PARI CITY VILLAGE COMMUNITY , PANTAI CERMIN DISTRICT, SERDANG BEDAGAI REGENCY - Yanti, Eli Delvi; Wahyono, Teguh; Sari, Wahyu Indah (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This study aims to find out how the development of village apparatus performance in realizing service improvement for the community in Pari City Village, Pantai Cermin District, Serdang Bedagai Regency. The Head of Desa and  all Village Officials in completing their duties, increasingly required hard work and optimal ability to facilitate the implementation of Pemerintahan tasks. The type of research that the author uses is qualitative descriptive research and explanatory surveys using case study strategies. Data collection techniques used in this study include Observation, Interview and Documentation. The results of this study concluded that there are efforts to improve the performance of the Pari City Village Apparatus in the implementation of government administrative tasks, especially the administration of Village Government needed by all people of Pari City Village, Pantai Cermin District, Serdang Bedagai Regency.